Determination of the mercury fraction linked to protein of muscle and liver tissue of Tucunaré (Cichla spp.) from the Amazon Region of Brazil - Vieira, José C. S. [UNESP]; Cavecci, Bruna [UNESP]; Queiroz, João V. [UNESP]; Braga, Camila P. [UNESP]; Padilha, Cilene C. F. [UNESP]; Leite, Aline L.; Figueiredo, Wllyane S.; Buzalaf, Marília A. R.; Zara, Luiz F.; Padilha, Pedro M. [UNESP] (Springer Nature, 2015)
This study used metalloproteomic techniques to characterize mercury (Hg)-bound proteins in the muscle and liver tissue of Tucunaré (Cichla spp.) collected at the Jirau Hydroelectric Power Plant in Madeira River Basin, Brazil. The proteome of the muscle and liver tissue was obtained after two steps of fractional precipitation and separating the proteins by 2-D polyacrylamide gel electrophoresis. Hg was identified and quantified in the protein spots by graphite furnace atomic absorption spectrometry after acid mineralization in an ultrasound bath. Hg with a molecular weight <20 kDa and a concentration between 13.30 and 33.40 mg g(-1) was found in the protein spots. These protein spots were characterized by electrospray ionization tandem mass spectrometry after trypsin digestion. From a total of 12 analyzed spots, seven proteins showing Hg biomarker characteristics were identified: parvalbumin and its isoforms, ubiquitin-40S ribosomal protein S27a, zinc (Zn) finger and BTB domain-containing protein 24, and dual-specificity protein phosphatase 22-B.